2020
DOI: 10.12669/pjms.36.3.938
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria (Moderate Albumin Excretion) and its relationship with Silent myocardial ischemia in  treatment naïve type II diabetic patients

Abstract: Objective: To determine the frequency of microalbuminuria (MAU) or Moderate Albumin Excretion (MAE) in treatment naïve type II diabetic patients and to compare the frequency of silent myocardial ischemia in treatment naive Type-II diabetic patients with and without microalbuminuria. Methods: It was a cross sectional survey conducted in the outpatient Department, Jinnah Hospital Lahore, from 30th May 2015 to 29th November 2015. There were 227 patients, (consecutive treatment naïve type II diabetic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…These are peripheral vascular disease, family history of myocardial ischemia, smoking, hypertension, and hyperlipidemia. There are other risk factors revealed to be associated with SMI or CAD in some studies, were not considered, except for retinopathy and hyperglycemia (HbA1c), for example: microalbuminuria (11) , autonomic neuropathy ( 12) , and apolipoprotein (a) (13) . This study had showed an interesting finding, that is: as the number of the basic risk factors increases, the results of positive EST (which most likely suggests the occurrence of SMI) increases in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These are peripheral vascular disease, family history of myocardial ischemia, smoking, hypertension, and hyperlipidemia. There are other risk factors revealed to be associated with SMI or CAD in some studies, were not considered, except for retinopathy and hyperglycemia (HbA1c), for example: microalbuminuria (11) , autonomic neuropathy ( 12) , and apolipoprotein (a) (13) . This study had showed an interesting finding, that is: as the number of the basic risk factors increases, the results of positive EST (which most likely suggests the occurrence of SMI) increases in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of diabetes target organ damage has been investigated in several studies, and a higher prevalence of silent CAD was demonstrated for retinopathy [20,26,55,93,94], neuropathy [11,[95][96][97][98][99][100], and nephropathy [59,[101][102][103][104], as well as for peripheral vascular disease [105][106][107][108][109][110][111][112].…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 99%
“…Diabetic nephropathy, is a well-known, strong predictor of CVD, and its association with silent CAD has been highlighted in several studies, even in the early stages of chronic renal disease [59,[101][102][103][104]. Microalbuminuria, a marker of incipient nephropathy, has been shown to be significantly associated with silent CAD, and is a powerful predictor of the disease [60,[100][101][102][103]. Al-Humaidi et al [59] demonstrated that myocardial abnormalities detected by SPECT in T2DM, correlates with nephropathy.…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 99%